KAJIAN KESALAHAN BERBAHASA INDONESIA DALAM POSTINGAN TWITTER GENERASI MILENIAL: PERSPEKTIF PENDIDIKAN BAHASA - Nisa Wati, Pratiwi; Suparmin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the types of Indonesian language errors found in Twitter posts among the millennial generation. As one of the most popular digital communication platforms, Twitter is widely used to express ideas, opinions, and emotions, yet it often features linguistic inaccuracies. Using a descriptive qualitative method, the research collected data from users’ tweets and analyzed them based on linguistic rules in accordance with the Kamus Besar Bahasa Indonesia (KBBI). The findings reveal various types of errors, including incorrect capitalization, use of non-standard words, letter redundancy, mixing with foreign languages, as well as morphological and syntactic mistakes. Contributing factors include limited language mastery, informal communication habits, and the influence of digital trends among millennials. These results highlight the importance of raising greater language awareness and the role of education in fostering proper use of Indonesian according to linguistic norms, particularly in the context of social media.